Application of the New Islamic Style Concept at Hotel Narapati Indah Syariah Boutique & Convention - Gissa Nurhalisa; Rangga Firmansyah; Ariesa Farida; M.Togar Mulya Raja (Pendhapa, 2022)
Sharia hotels are accommodation services needed by Muslim tourists which have increased since the government began developing halal tourism. In the design of the Narapati hotel which refers to Ministerial regulation No. 2 of 2014 concerning guidelines for the operation of the Sharia hotel business with a classification of Hilal 1, which consists of several aspects. It is necessary to pay attention to the separation between men and women on each floor or room area, facilities, and circulation of visitors. The application of the latest Islamic concept that combines the classic style (existing hotel) with Islamic architecture (Islamic patterns such as calligraphy, geometric, arabesque, arch), can present an attractive form with a current, unique and luxurious feel, the application of colors that follow the Islamic sunnah can bring blessings. These things are applied in order to stay away from deviant behavior, create a safe, comfortable atmosphere for hotel visitors so as to generate interest in coming back.